DEVELOPMENT OF SPECIAL PHYSICAL TRAINING OF GRECO-ROMAN WRESTLERS WITH THE HELP OF SPECIAL SIMULATORS (Conferencea, 2023)
This article substantiates the effectiveness of Greco-Roman wrestlers’ flexibility development technology based on the use of special simulators and exercises.